Standard dermoscopy and videodermoscopy as tools for medical student dermatologic education - Hyunje G. Cho; Sarah L. Sheu; Audris Chiang; Kristin M. Nord (Mattioli1885, 2018)
Background: Standard dermatoscopy improves the medical students' ability to identify malignant skin lesions by noninvasive inspection of microstructures in the epidermis and superficial dermis. Videodermatoscopy allows for higher magnification, concurrent dermoscopic examination by multiple users. The purpose of this study is to understand the role of standard dermoscopy and videodermoscopy training in medical student dermatologic education. Objectives: To evaluate the effect of instruction using standard dermoscopy and videodermoscopy on the self-reported confidence and objective ability of medical students to identify benign and malignant skin lesions. Methods: Ninety second-year medical students were invited to receive a 45-minute lecture on general dermatologic topics and a 7-minute training session with either a standard dermatoscope or videodermatoscope. A total of 54 students completed an identical pre-test and post-test before and after the training session that included 13 knowledge-based analytic and image identification questions. Results: Both groups reported increased confidence in the ability to identify benign and malignant lesions after the training session. The combined group demonstrated an improved ability to identify dermoscopic features of benign and malignant skin lesions with a mean (SD) pre-test score of 3.4 (1.4) and a mean post-test score of 6.0 (1.6) out of 9 knowledge-based questions (p<0.001); however, there was no difference noted between the two interventions. Conclusions: Instruction using either a standard dermatoscope or a videodermatoscope can increase medical students' confidence and accuracy in identifying benign and malignant skin lesions.